The gut–lung axis: a new perspective on the impact of atmospheric particulate matter exposure on chronic obstructive pulmonary disease - Pang, Xichen; Huang, Ping; Huang, Sha; Liu, Xiaoju (Frontiers in Immunology, 2025)
Environmental pollution is a serious public health problem closely related to various chronic respiratory diseases, such as chronic obstructive pulmonary disease (COPD), bronchial asthma, and lung malignancies. Atmospheric particulate matter (PM) is an important component of environmental pollution, and its influence on COPD has been shown to be related to inflammation, oxidative stress, immune imbalance, abnormal cell death, and cell aging. A growing body of evidence has shown that an imbalance of the lung and intestinal microbiota, as well as changes in metabolites, is closely related to the occurrence and development of PM-induced COPD. PM exposure damages the respiratory system and alters the structure and activity of the gut microbiome. The metabolites produced by the gut microbiome, in turn, disrupt airway immunity and exacerbate respiratory inflammation. Therefore, the bidirectional influence of PM on the gut–lung axis has attracted widespread attention. This review explores the mechanisms by which PM causes oxidative stress damage to the lungs and intestines, as well as the characteristics of the resultant immune imbalance and changes in the microbiota and metabolite products. It also describes how PM disrupts barrier function through microecological imbalance and how it participates in the progression of COPD via the gut–lung axis. These mechanisms highlight the potential of targeting the microbial flora as a new approach for treating COPD caused by environmental pollution.